News media influence on public trust in bike-sharing operators in Singapore - WONG, Leonard (Institutional Knowledge at Singapore Management University, 2020)
Purpose: The overnight introduction of tens of thousands of dockless bike-share bicycles in Singapore with its indiscriminate parking drew the attention of the media, which generated extensive news reports on the activities carried out by bike-sharing operators. Given the meteoric rise and fall of the industry, this study examines the influence of agenda-setting of news reporting on the public’s perception of the industry and the impact on the firms’ corporate reputation. Design/methodology/approach: Utilizing the Reputation Quotient Index, the study content analyzed 147 textual data of online reports which were crawled over two years between 2017 and 2018 from six mainstream news organizations. Findings: Our findings showed that the news reports carried more negative frames in the headlines and body content. It also found that only five out of six dimensions of the Index were emphasized with varying degrees of importance, indicating that the corporate reputation as determined by the media reports did not collectively represent the operators’ past actions and results with valued outcomes. Practical implications: Practical implications discussed included the need to integrate corporate strategies into public relations programs and the importance of engaging the media to demonstrate congruence between business objectives and positive social impact on society. Originality/value: Although the study limited its data collection only to online media reports, it is one of the few research to provide empirical evidence concerning the media’s influence on the public’s perceptions and reputation of the nascent bike-sharing industry.